Computer storage and retrieval of generic chemical structures in patents. 12. Principles of search operations involving parameter lists: matching-relations, user-defined match levels, and transition from the reduced graph search to the refined search - Dethlefsen, Winfried; Lynch, Michael F; Gillet, Valerie J; Downs, Geoffrey M; Holliday, John D; Barnard, John M (Journal of chemical information and computer sciences, 1991)
Continuation of the discussion from the previous paper (see Journal of Chemical Information and Computer Sciences 31 (2) May 91, 233-253), dealing with the establishment of consistent framework for the discussion and treatment of generic chemical structures in patents. Describes the nature of the search operations and the use of parameter lists representing both specifically and generically described parts within generic full structures as the basis for the matching operation prior to the refined search on the Extended Connection Table Representation (ECTR). Considers the possibility of extending the matching operations in order to implement user-defined levels of search and refinement of the search. 00 Original abstract--amended